The start of a conversation on the value of New Zealand's social capital - Margreet Frieling (New Zealand Government, The Treasury, 2018)
This paper describes a conceptual framework for the key components of social capital, as a first step towards its measurement as part of the Treasury's Living Standards Framework. It proposes a definition of social capital as the social connections, attitudes and norms that contribute to societal wellbeing by promoting coordination and collaboration between people and groups in society.
Keywords: 330